Reception and transmition of Civil Procedure Law: interpretations on an issue without borders - Caponi, Remo (Civil Procedure Review, 2010)
The text analyses the reception of procedural institutes in traditional and modern forms, studying the problems that could arise, for instance, in translations of law texts, and the respective outcomes in terms of culture exchange.